Cell-free DNA screening for trisomies 21, 18, and 13: Clinical application and accuracy evaluation - Xiangmei Sun; Yuyi Ying; Caiping Chen; Xiaoliang Shi (PLoS ONE, 2025)
Background Cell-free DNA (cf-DNA) screening for common trisomies has been increasingly assimilated into prenatal care. In this study, we evaluated the Z-score accuracy and the effectiveness of non-invasive prenatal testing (NIPT) for trisomies 21, 18, and 13 using cf-DNA, and further analyze pregnancy outcomes of NIPT-positive pregnant women. Methods This retrospective study analyzed pregnancies that yielded positive NIPT results at Shaoxing Maternity and Child Health Care Hospital between 01/01/2017 and 31/12/2022. Invasive prenatal diagnosis (IPD) confirmed the positive NIPT findings. Logistic regression analysis was applied to correlation analysis of Z-scores and positive predictive value (PPV). Accuracy of Z-score was evaluated through receiver operating characteristic (ROC) curve analysis. Data regarding basic characteristics, prenatal diagnosis results, and pregnancy outcomes were collected. Results In total,257 high-risk cases of trisomy 21, 18, and 13 were identified. Among these,193 pregnancies underwent invasive prenatal diagnosis (IPD) in our institution, the PPV was 75.44% for T21,45.28% for T18, and 17.86% for T13. A significant association between Z-scores and PPVs were revealed by logistic regression(p < 0.05). The ROC curve analysis revealed optimal cutoff values of 7.231 for T21, 5.245 for T18, and 7.504 for T13. The corresponding areas under the curve (AUC) were 0.954, 0.941, and 0.924, respectively. Moreover, the PPV was statistically higher in the very-high-risk (VHR) group than in the general high-risk (GHR) group. In terms of pregnancy outcomes,98.51% (132/134) of pregnancies identified with chromosomal abnormalities were terminated, whereas 98.89% (89/90) of those diagnosed with false-positive results were carried to term. Conclusions The study demonstrates that the Z-score is valuable in accurately assessing NIPT results. Consequently, clinicians can provide more efficient prenatal genetic counseling by utilizing a specific reference value for the Z-score.